2012
DOI: 10.1038/onc.2012.315
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in isocitrate dehydrogenase 1 and 2 occur frequently in intrahepatic cholangiocarcinomas and share hypermethylation targets with glioblastomas

Abstract: Mutations in the genes encoding isocitrate dehydrogenase, IDH1 and IDH2, have been reported in gliomas, myeloid leukemias, chondrosarcomas, and thyroid cancer. We discovered IDH1 and IDH2 mutations in 34 of 326 (10%) intrahepatic cholangiocarcinomas. Tumor with mutations in IDH1 or IDH2 had lower 5-hydroxymethylcytosine (5hmC) and higher 5-methylcytosine (5mC) levels, as well as increased dimethylation of histone H3K79. Mutations in IDH1 or IDH2 were associated with longer overall survival (p = 0.028) and were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
316
4
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 348 publications
(337 citation statements)
references
References 46 publications
14
316
4
3
Order By: Relevance
“…Such clustering enables early detection of IDH1 mutation in circulating tumour DNA as a way to screen for potential ICC tumours. In contrast to many previous studies 23,24,41 , mutations in IDH2 were not found in our cohort of ICC patients. Mutations in IDH1 and IDH2 have been found to cause a gain-of-function in the production of 2-hydroxyglutarate and to alter histone and DNA methylation 60 .…”
Section: Mutationcontrasting
confidence: 54%
“…Such clustering enables early detection of IDH1 mutation in circulating tumour DNA as a way to screen for potential ICC tumours. In contrast to many previous studies 23,24,41 , mutations in IDH2 were not found in our cohort of ICC patients. Mutations in IDH1 and IDH2 have been found to cause a gain-of-function in the production of 2-hydroxyglutarate and to alter histone and DNA methylation 60 .…”
Section: Mutationcontrasting
confidence: 54%
“…IDH1 and 2 mutations, recently shown to be among the most frequent mutations in intrahepatic cholangiocarcinomas, 48,50 were absent in intraductal tubulopapillary neoplasms. Likewise, loss of SMAD4 was restricted to a single example.…”
Section: Molecular/immunohistochemical Featuresmentioning
confidence: 95%
“…On the other hand, single CDKN2A, IDH2, MET, and RET somatic mutations were observed only in the invasive counterpart of matched samples. IDH2 mutations have never been described in gastric cancers and are rare in the gastrointestinal tract, with the exception of intrahepatic cholangiocarcinomas [25]. The diagnostic impact of CDKN2A, MET, and RET in discriminating among preinvasive and early invasive lesions should be tested in a larger prospective series of HG-IEN, whereas the germline variants in ATM, KDR, KIT, PIK3CA, and TP53 that are shared by both HG-IEN and EGC lesions should be evaluated for their potential to identify predisposition to gastric cancer.…”
Section: Discussionmentioning
confidence: 99%